If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x++4=5-3x
We simplify the equation to the form, which is simple to understand
-2x+4=5-3x
We move all terms containing x to the left and all other terms to the right.
-2x+3x=+5-4
We simplify left and right side of the equation.
+1x=+1
We divide both sides of the equation by 1 to get x.
x=1
| -8x+7*0=-56 | | 12-2x=3x+4 | | 10-3x=3x-2 | | 3x-7=13-2x | | 9x-2=28-x | | .5x+6=.33x | | 9x-2=28-2 | | 14(t-6)+4t=6(3t+5)-12 | | -8x+7-0=-56 | | 5z=-3(z+8) | | 3x+9=7x-9 | | -1[a-1(a+-5)]+-3=-5-1(-9+-5) | | 5c=-3(2+8) | | 12(3x+6)-7(2x-6)=2x-26 | | 2(3x-6)=3(x-9) | | 14x-1-5x=-28+12x | | 3x-4(2x+2)=2 | | 8w-10= | | -x+6=-30 | | 5x+12=102 | | 5x=-1.8 | | 6x^2-7=10 | | 7u=4 | | -4x-4=6-3x | | 7x+4=5x+17 | | v-18=3v-7+3 | | a=b-4c | | 4+11s-2=6s+10-3s | | 8y-y=6 | | 8z-48=-16 | | -[a-(a-5)]-3=-5-(-9-5) | | 63=-2x-5x+7 |